2021
DOI: 10.31234/osf.io/s3anz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why consumers shift from single-use to reusable drink cups: An empirical application of the stage model of self-regulated behavioural change

Abstract: Using single-use drink cups contributes to environmental issues like littering, resource depletion, and carbon dioxide emissions and thus comes into conflict with the UN Sustainable Development Goals. There are reusable alternatives to such single-use cups available to the general public, but uptake has so far been limited. To explain what factors are associated with using single-use cup alternatives, we apply the stage model of self-regulated behavioural change in a cross-sectional questionnaire study, N = 57… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Managerial implications also emerge from this research in which the environmental cause is the adoption of RCCs to avoid environmental issues like littering, resource depletion and carbon dioxide emissions, and, thus, is in conflict with the UN Sustainable Development Goals (Keller et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managerial implications also emerge from this research in which the environmental cause is the adoption of RCCs to avoid environmental issues like littering, resource depletion and carbon dioxide emissions, and, thus, is in conflict with the UN Sustainable Development Goals (Keller et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Managerial implications also emerge from this research in which the environmental cause is the adoption of RCCs to avoid environmental issues like littering, resource depletion and carbon dioxide emissions, and, thus, is in conflict with the UN Sustainable Development Goals (Keller et al, 2021). First, it is reassuring that higher levels of cause involvement lead to higher levels of positive attitudes and behavioural intentions towards the cause (i.e.…”
Section: Ccij 274mentioning
confidence: 89%
“…Measures are needed to effectively promote more sustainable customer behaviour. However, before such measures become reality, research is still required, and interventions that use phase‐specific concepts need to be tested experimentally in the field (Gelino et al, 2021; Keller et al, 2021; Lange & Dewitte, 2019). While in our opinion there would be numerous opportunities to systematically test subtle measures in real‐life settings with high external validity, unfortunately no real online store operators were willing to be partners for the experiment.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…A study on SUPs consumption has revealed that some people favor attitudes towards SUPs and consume them equally, some are potential avoiders who sometimes consume and sometimes avoid SUPs and avoiders who avoid consumption of SUPs (Adam et al, 2021). For selfregulated behavioral change in consumption of SUPs require awareness, negative emotions and individuals responsibility on social norms (Keller et al, 2021). The behavior of an individual on use of SUPs has four stages; predecisonal, preactional, actional and postactional.…”
Section: Knowledge Regarding Single-use Plasticmentioning
confidence: 99%
“…The behavior of an individual on use of SUPs has four stages; predecisonal, preactional, actional and postactional. A person require awareness and knowledge in each stage and require to make decision as per the stages (Keller et al, 2021). The selfregulated behavior change is proposed to enhance the reduction of plastic pollution (Adam et al, 2021).…”
Section: Knowledge Regarding Single-use Plasticmentioning
confidence: 99%